2021
DOI: 10.1073/pnas.2109517118
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain containing 9 (BRD9) regulates macrophage inflammatory responses by potentiating glucocorticoid receptor activity

Abstract: In macrophages, homeostatic and immune signals induce distinct sets of transcriptional responses, defining cellular identity and functional states. The activity of lineage-specific and signal-induced transcription factors are regulated by chromatin accessibility and other epigenetic modulators. Glucocorticoids are potent antiinflammatory drugs; however, the mechanisms by which they selectively attenuate inflammatory genes are not yet understood. Acting through the glucocorticoid receptor (GR), glucocorticoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
(67 reference statements)
3
14
0
Order By: Relevance
“…These analyses suggest that human BRD9 is well conserved, and may indicate that rare BRD9 missense variants are not readily tolerated in humans. This would be consistent with the critical role of BRD9 in the gene expression regulatory functions of the ncBAF chromatin remodeling complex 20 , and potentially also the antiviral IFN system [16][17][18] .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…These analyses suggest that human BRD9 is well conserved, and may indicate that rare BRD9 missense variants are not readily tolerated in humans. This would be consistent with the critical role of BRD9 in the gene expression regulatory functions of the ncBAF chromatin remodeling complex 20 , and potentially also the antiviral IFN system [16][17][18] .…”
Section: Resultssupporting
confidence: 80%
“…BRD9 defines the ncBAF chromatin remodeling complex that, together with the canonical STAT1-STAT2-IRF9 transcription factor complex, has previously been identified as an important contributor to efficient IFN-stimulated gene transcription and antiviral immunity [16][17][18] . Our evaluation of BRD9 genetic variants has now identified that severely truncated ultra-rare BRD9 LOF alleles exist in the human population, and revealed that under conditions where only these alleles are present there is compromised ability of IFN to fully protect cells against virus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, most DEGs are down-regulated by inhibitor treatment, in agreement with the cluster results showing dampened induction of genes 4 h post Lipid A stimulation. Finally, to determine how well each BRD9 inhibitor treatment correlated with Brd9 genetic deletion, we made use of an RNA-seq dataset comparing LPS + IFN-γ treatment in BMDM derived from wild-type or Brd9f/f;LysM-Cre animals, in which Brd9 is conditionally deleted in the myeloid lineage ( 22 ). Using gene set enrichment analysis (GSEA), we found that genes down-regulated in BI-9564-, dBRD9-, and I-BRD9-treated Lipid A-induced macrophages were positively correlated with genes down-regulated in LPS+IFN-γ–treated Brd9 knockout macrophages with normalized enrichment scores (NES) of 2.47, 2.33, and 2.35, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Publicly available data were processed using HOMER version 4.10 (Christopher Benner, HOMER, http://homer.ucsd.edu/homer/index.html ). The following database deposition numbers are given: for RNA-seq of Irf3 −/− , Ifnar −/− , Trif −/− , Myd88 −/− , Pam3, and CHX treatment, GEO GSE67355 ( 2 ); for RNA-seq of LysM-Cre BRD9 knockout, Sequence Read Archive (SRA) PRJNA731887 ( 22 ); for ChIP-seq of IRF3, GEO GSE67357 ( 2 ); IRF9, STAT1, and STAT2 in IFNb stimulation, GEO GSE115435 ( 19 ); PU.1, GEO GSE38379 ( 25 ); and p65, GEO GSE106701 ( 26 ).…”
Section: Data Availabilitymentioning
confidence: 99%